Investigation into Prevalence and Factors Influencing HIV among Sexually Active Youth in Nigeria - Victoria, Tawose Oluwatomisin; Oboh, Joy Isioma; Doyinsola, Afonja Olufunmilayo; Fagbamigbe, Adenike O; Olushola-Jimoh; Adebanke, Tolulope; Annabelle, Alimi Grace O. (American Journal of Biomedicine and Pharmacy, 2024)
Introduction: Since the first identification of AIDS in 1981, HIV/AIDS has become a global epidemic, severely impacting health development and life expectancy, particularly in Sub-Saharan Africa. In Nigeria, the epidemic has affected various communities with fluctuating prevalence rates over the decades. This study aims to analyze the sexual behavior, knowledge of STIs and HIV, and preventive practices among sexually active youths in Nigeria, focusing on understanding the factors influencing HIV infection risk. Objective: To assess the prevalence of HIV and identify predictors among sexually active youths in Nigeria, evaluating the association between demographic factors, knowledge of HIV, and preventive behaviors. Method of Analysis: A cross-sectional, population-based study was conducted with 422 sexually active youths. Data were analyzed using SPSS version 22 with descriptive and inferential statistics, including chi-square tests at a significance level of p<0.05. Results: The study revealed that 33.7% of respondents were aged 15-21 years, and 66.3% were aged 22-28 years. The gender distribution showed 60.4% females and 39.6% males. The HIV prevalence among females was 3.9% compared to 2.7% among males (χ² = 4.58, p = 0.032). Marital status showed that those living with a sex partner had the highest prevalence (7.0%). Knowledge of HIV transmission was generally high, but misconceptions persisted. Notably, 57.4% perceived no risk of HIV, and those with this perception had a higher HIV prevalence (χ² = 6.12, p = 0.013). Conclusion: The study highlights significant gaps in HIV knowledge and preventive practices among Nigerian youths. Although there is awareness of HIV transmission, misconceptions and risk perception issues persist. To enhance sexual health outcomes, comprehensive sexual education programs are recommended, with a focus on correcting misconceptions, promoting condom use, and addressing gender disparities in HIV prevalence. Increased accessibility to sexual health services, particularly in rural areas, is also crucial.